The dynamics of composite stock price index market: A review of key economic factors - Hasanudin Hasanudin (Universitas Ahmad Dahlan, 2025)
The capital market plays a pivotal role as a platform for both individuals and financial institutions to invest. This research aims to investigate how various factors, including the Dow Jones Index, interest rates, inflation, and the exchange rate of the Rupiah, influence the performance of the Composite Stock Price Index from 2018 to 2022. The study employs a non-probability Sampling technique, specifically purposive sampling, with 60 samples selected for analysis. A quantitative research design is applied, focusing on the aforementioned variables, and employing a saturated sampling approach. The data is analyzed through multiple linear regression using SPSS version 23. These findings suggest that, of the research hypotheses developed, only one is accepted, inflation has a positive influence on Composite Stock Price Index. Then, in contrast to the hypothesis development, which is pointing in a positive direction, the Dow Jones Index has a positive influence on Composite Stock Price Index, but no significant. Interest rates and exchange rates have no positive effect on Composite Stock Price Index. Despite this, the importance of the other factors remains significant, as they are essential for understanding the behavior of the Indonesian stock market. The research emphasizes the need for a holistic approach to forecasting or analyzing stock market trends.